2016
DOI: 10.1371/journal.pone.0166966
|View full text |Cite
|
Sign up to set email alerts
|

M30 Antagonizes Indoleamine 2,3-Dioxygenase Activation and Neurodegeneration Induced by Corticosterone in the Hippocampus

Abstract: Monoamine oxidases (MAO), downstream targets of glucocorticoid, maintain the turnover and homeostasis of monoamine neurotransmitters; yet, its pathophysiological role in monoamine deficiency, oxidative stress and neuroinflammation remains controversial. Protective effects of M30, a brain selective MAO inhibitor with iron-chelating antioxidant properties, have been shown in models of neurodegenerative diseases. This study aims to examine the neuroprotective mechanism of M30 against depressive-like behavior indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Hippocampus is also a target of stress hormones, and stress and high glucocorticoids can affect the hippocampal neuroplasticity 12. It is reported that TPH2 gene is expressed in the hippocampus and raphe nuclei,13 and IDO1 has a certain effect on the function and structure of hippocampal neurons 14. Therefore, hippocampus may be a key region to observe the stress-induced changes in TPH2 and IDO1 in the 5-HT system.…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampus is also a target of stress hormones, and stress and high glucocorticoids can affect the hippocampal neuroplasticity 12. It is reported that TPH2 gene is expressed in the hippocampus and raphe nuclei,13 and IDO1 has a certain effect on the function and structure of hippocampal neurons 14. Therefore, hippocampus may be a key region to observe the stress-induced changes in TPH2 and IDO1 in the 5-HT system.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an MAO inhibitor, phenelzine, better prevents the recurrence of depressive symptoms, compared to tricyclic antidepressants, nortriptyline (Georgotas et al, 1989 ). In addition to changing neurotransmitter levels in the brain, inhibition of MAO leads to a neuroprotective effect against glucocorticoid (GC)-induced apoptosis (Johnson et al, 2010 ; Lam et al, 2016 ). M30, an MAO inhibitor with iron-chelating antioxidant properties, prevents corticosterone-induced alteration in the hippocampus, such as activation of indoleamine 2,3-dioxygenase, hippocampal apoptosis, loss of synaptic proteins and neurodegeneration and neuroinflammation (Lam et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to changing neurotransmitter levels in the brain, inhibition of MAO leads to a neuroprotective effect against glucocorticoid (GC)-induced apoptosis (Johnson et al, 2010 ; Lam et al, 2016 ). M30, an MAO inhibitor with iron-chelating antioxidant properties, prevents corticosterone-induced alteration in the hippocampus, such as activation of indoleamine 2,3-dioxygenase, hippocampal apoptosis, loss of synaptic proteins and neurodegeneration and neuroinflammation (Lam et al, 2016 ). Selective MAO-A inhibition with pirlindole abolishes the alteration induced by chronic mild stress, such as behavioral changes in forced swimming test and the dendritic atrophy of granule neurons, but promotes adult neurogenesis in the hippocampus of rats exposed to chronic mild stress (Morais et al, 2014 ), indicating the effectiveness of MAO-A inhibition for stress-induced neurobiological alterations in the brain.…”
Section: Introductionmentioning
confidence: 99%